The estimated health impact of sodium reduction through food reformulation in Australia: A modeling study - Kathy Trieu (Public Library of Science (PLoS), 2021)
Background The Australian Government recently established sodium targets for packaged foods to encourage voluntary reformulation to reduce population sodium consumption and related diseases. We modeled the health impact of Australia’s sodium reformulation targets and additional likely health gains if more ambitious, yet feasible sodium targets had been adopted instead. Methods and findings Using comparative risk assessment models, we estimated the averted deaths, incidence, and disability-adjusted life years (DALYs) from cardiovascular disease (CVD), chronic kidney disease (CKD) and stomach cancer after implementation of (a) Australia’s sodium targets (overall and by individual companies); (b) United Kingdom’s targets (that covers more product categories); and (c) an optimistic scenario (sales-weighted 25th percentile sodium content for each food category included in the UK program). We used nationally representative data to estimate pre- and post-intervention sodium intake, and other key data sources from the Global Burden of Disease study. Full compliance with the Australian government’s sodium targets could prevent approximately 510 deaths/year (95% UI, 335 to 757), corresponding to about 1% of CVD, CKD, and stomach cancer deaths, and prevent some 1,920 (1,274 to 2,600) new cases and 7,240 (5,138 to 10,008) DALYs/year attributable to these diseases. Over half (59%) of deaths prevented is attributed to reformulation by 5 market-dominant companies. Compliance with the UK and optimistic scenario could avert approximately an additional 660 (207 to 1,227) and 1,070 (511 to 1,856) deaths/year, respectively, compared to Australia’s targets. The main limitation of this study (like other modeling studies) is that it does not prove that sodium reformulation programs will prevent deaths and disease events; rather, it provides the best quantitative estimates and the corresponding uncertainty of the potential effect of the different programs to guide the design of policies. Conclusions There is significant potential to strengthen Australia’s sodium reformulation targets to improve its health impact. Promoting compliance by market-dominant food companies will be critical to achieving the potential health gains. Kathy Trieu and colleagues model the estimated health impact of sodium reformulation targets in Australia. Author summary Why was this study done? High sodium intake increases blood pressure and the risk of heart disease, chronic kidney disease (CKD), and stomach cancer. Almost all adults in Australia and worldwide exceed sodium intake recommendations. To help reduce population sodium intakes, the Australian Government recently established sodium targets for packaged foods to encourage voluntary reformulation. However, the potential health gains of these targets are not known. What did the researchers do and find? We modeled the potential health gains that could be achieved if all food companies met Australia’s sodium targets and what additional health gains could be achieved if Australia adopted more ambitious targets. Using mathematical models, reductions in population sodium intake after implementation of sodium targets were calculated and translated into expected changes in blood pressure and health gains related to heart disease, CKD, and stomach cancer. Full compliance with Australia’s sodium targets could prevent approximately 510 deaths/year. Over half of these deaths could be prevented by just 5 food companies complying with the targets. If Australia adopted the sodium targets already implemented in the United Kingdom or a more ambitious, yet feasible set of targets, an additional 660 and 1,070 deaths/year, respectively, could be averted. What do these findings mean? This study demonstrates that national sodium reformulation targets could be an effective strategy to prevent death and disability associated with heart disease, CKD, and stomach cancer. Australia’s sodium reformulation targets could achieve greater public health benefits if these targets were mandatory, targeted more food categories, and included more stringent targets. To maximize the potential of Australia’s current sodium targets, promoting full compliance across dominant food companies could help to achieve health gains.